Hubungan dukungan keluarga dengan Kepatuhan minum obat pada Penderita tb paru - Asra - Septia; Siti Rahmalia HD; Febriana - Sabrian (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
This study aimed to determine the relationship between family support and tuberculosis drug’s compliance. This was analytic research with cross sectional approach the dynamics of the correlation between the two variables simultaneously at a time. The total number of respondent was 58 choosed by accidental sampling technique with inclusion and exlusion criteria. The instrument was questionnaires with 19 questions that has been tested for validity and reliability. The data were analyzed by univarate and bivariate with chi- square test. The result showed that there was relationship between family support and tuberculosis drug’s compliance with p value=0,036. Based on these results, it is expected to further improve the family members of the family support that affect medication adherence of TB patients. Keywords: family support, compliance, pulmonary tuberculosis